Crystal structure of baryte from Mine du Pradet (France) - Paulsen Christian; Galéa-Clolus Valérie; Pöttgen Rainer (Zeitschrift für Kristallographie - New Crystal Structures)
BaSO4, orthorhombic, Pnma (no. 62), a = 8.8806(8) Å, b = 5.4539(5) Å, c = 7.1570(7) Å, V = 346.64(6) Å3, Z = 4, Rgt (F 2) = 0.0141, wRref (F 2) = 0.0329, T = 293 K.